2020
DOI: 10.3390/v12091005
|View full text |Cite
|
Sign up to set email alerts
|

Going beyond Integration: The Emerging Role of HIV-1 Integrase in Virion Morphogenesis

Abstract: The HIV-1 integrase enzyme (IN) plays a critical role in the viral life cycle by integrating the reverse-transcribed viral DNA into the host chromosome. This function of IN has been well studied, and the knowledge gained has informed the design of small molecule inhibitors that now form key components of antiretroviral therapy regimens. Recent discoveries unveiled that IN has an under-studied yet equally vital second function in human immunodeficiency virus type 1 (HIV-1) replication. This involves IN binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 224 publications
(348 reference statements)
0
25
0
Order By: Relevance
“…Thus, the maturation status of extracellular defective viruses becomes increasingly important for estimating their potential immunogenicity and our novel FRET labeling system would be suitable for investigating this matter. In addition, the viral integrase has been also shown to be necessary for correct HIV-1 maturation ( Fontana et al, 2015 ; Kessl et al, 2016 ; Elliott and Kutluay, 2020 ) and its mechanism of action could also be explored using HIV-1 Gag-iFRET.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the maturation status of extracellular defective viruses becomes increasingly important for estimating their potential immunogenicity and our novel FRET labeling system would be suitable for investigating this matter. In addition, the viral integrase has been also shown to be necessary for correct HIV-1 maturation ( Fontana et al, 2015 ; Kessl et al, 2016 ; Elliott and Kutluay, 2020 ) and its mechanism of action could also be explored using HIV-1 Gag-iFRET.…”
Section: Discussionmentioning
confidence: 99%
“…The canonical role of HIV-1 IN is to catalyze insertion of the reverse transcribed viral DNA into host chromatin [ 4 ]. However, IN mutations have been identified that not only impair viral integration, but also influence other steps of the viral lifecycle, including maturation (reviewed in [ 5 , 6 ]). Mutations that specifically impair viral DNA integration are known as class I, whereas class II mutations also affect other steps of the viral lifecycle [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned before, recent works revealed that in HIV-1, IN is also an RBP with an essential role in virion morphogenesis, related to its ability to bind gRNA 8 25 26 . In fact, IN interacts with specific sites within gRNA ensuring the correct localization of viral RNP inside the capsid (reviewed in 27 ). Aberrant virions are obtained when IN-gRNA interaction is abolished, highlighting the importance of the proper formation of IN-containing RNPs for HIV-1 infection ( 8,25,28 ).…”
Section: Introductionmentioning
confidence: 99%